PENEGAKAN HAK PEKERJA HARIAN LEPAS (DAILY WORKER) BERDASARKAN HUKUM POSITIF DI INDONESIA - Yulinar, Intan Khofifah; Sarjana, I Made (Kertha Negara : Journal Ilmu Hukum; Vol 11 No 5 (2023), 2023)
The purpose of this study is to analyze the rights of casual daily workers in positive legal rules in Indonesia accompanied by the responsibilities of employers when these rights are not fulfilled. This research uses normative research methods with a descriptive approach. The results obtained from this study are the rights of freelance daily workers regulated in the labor law, the Ciptaker Law and its derivative rules, namely minister law number 100 and government law number 35 which in essence the rights of freelance daily workers are wages and health insurance. Employers who have obligations in terms of wages to employees when they do not fulfill their obligations in terms of wages to workers will be subject to administrative sanctions based on the results of labor inspectors. The drawback is that there is still no enforcement to employers when they do not fulfill workers' rights in terms of health insurance as stipulated in government law number 35.